2022
DOI: 10.1039/d2dt00902a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structural characterisation of solid titanium(iv) phosphate materials by means of X-ray absorption and NMR spectroscopy

Abstract: Solid titanium phosphate, TiP, materials hold great promise for wastewater treatment for removal of metal ions and complexes. A series of TiP materials, synthesised at mild conditions and short reaction...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Sodium dihydrogen phosphate monohydrate, NaH 2 PO 4 ·H 2 O, was purchased from Merck at analytical grade quality and used without further purification. Titanium bis­(hydrogenphosphate) dihydrate, α-Ti­(HPO 4 ) 2 ·H 2 O, was synthesized in aqueous conditions according to a procedure described elsewhere …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sodium dihydrogen phosphate monohydrate, NaH 2 PO 4 ·H 2 O, was purchased from Merck at analytical grade quality and used without further purification. Titanium bis­(hydrogenphosphate) dihydrate, α-Ti­(HPO 4 ) 2 ·H 2 O, was synthesized in aqueous conditions according to a procedure described elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…The P-edge XANES spectra analyzed in this study have been reported in already published papers, ,, where the experimental conditions and procedures, and energy calibration, have been described in detail. All data were collected at the bending magnet beamline 8 at the Synchrotron Light Research Institute (SLRI) in Nakhon Ratchasima, Thailand …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations